The role of independent education in students' mastery of knowledge - Kuranbayeva Makhliyo (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In this article, people can find information about importance of independent learning in educating students,types of independent learning skills, methods and factors influencing attainment of knowledge by learners.